Regional Development Strategy Based on Superior Commodities, Masalle District, Enrekang Regency - Nur Fitri Ramadhani; Budimawan; Danial Useng; Muslim Salam; Arifuddin Akil; Ria Wikantari (Journal of Public Administration and Government, 2022)
Masalle District is one of Enrekang Regency's sub-districts with high agricultural potential. According to the Enrekang Regency Spatial Plan 2011-2031, Masalle District is designated as a center for horticultural crop production and as a designated area for the development of large livestock. Masalle District, on the other hand, is located in an area prone to fault zones and landslides. As a result, the purpose of this research is to identify superior commodities, establish regional zones, determine land carrying capacity based on land capabilities, and develop a regional development strategy based on superior commodities in the Masalle District. Field observations, expert interviews, and related literature were used to collect data. Purposive sampling was used to select respondents. The method of analysis employs LQ (Location Quotient) analysis, Klassen Typology, Scalogram, analysis of land carrying capacity based on land capability, and Analytic Hierarchy Process (AHP) - Strength, Weakness, Opportunities, and Threats (SWOT). According to the findings, the main commodities in Masalle District were peanuts, red beans, carrots, and goats as the leading commodities that developed and grew quickly, green onions as the leading commodity of fast growing, and cassava, sweet potatoes, potatoes, cabbage, tomatoes, bananas, coffee, and free-range chicken as a commodity developed under pressure. There are a total of four regional zones. The land has a carrying capacity of 1.53, indicating that it has optimal development potential while maintaining environmental balance. In addition, the S-O strategy is one of eleven regional development strategies that can be used in conjunction with strategic priorities.